After fair trade: fair products - Diop, Demba (Technical Centre for Agricultural and Rural Cooperation, 1999)
Demba Diop, trained in accountancy and quality management, worked in his native Senegal in the 1980s as assistant manager at the Al Hanafiyatou development foundation. He established the Dutch foundation EcoFair in 1994 to help producers in the...